Penguatan Karakter Hidup Sehat melalui Permainan Konvensional sebagai Fondasi Menyongsong Generasi Emas 2045 - Nanang Purwanto; M Iqbal Maulana; Neila Putri Shofiyana; Imel Wijayanti; Nadila Erdina Putry (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
Conventional games are a national cultural heritage, now gradually fading and rarely found in society. This is due to the development of science and technology. This phenomenon was found among students at SDN 2 Jajar, Trenggalek Regency. Online games involve the sense of sight which is at risk of bad for children's motor and social development, while conventional games involve body parts to move, so that the body is healthier, stronger, and fitter. The population in the study included all children aged 6 to 12 years in Jajar Village. The sample included 31 students from grades one to six and 31 parents of SDN 2 Jajar students. Data collection techniques were through observation, interviews, and documentation. Data analysis techniques were descriptive qualitative. This paper explains efforts to arouse the enthusiasm and love of students at SDN 2 Jajar and Madrasah Ibtidaiyah Jajar for conventional games that are the foundation of a healthy lifestyle. The socialization was held on January 3-4, 2024, while practical activities were held on January 7 and 21, 2024. Conventional games that were socialized included Rangku Alu, Egrang, Bakiak, Gobak Sodor. The results of the socialization showed a positive response from students and parents/guardians of SDN 2 Jajar. The aim of this activity is to realize healthy children's characters to welcome the golden generation of 2045.